The Impact Of Tourism Special Economic Zones (Sezs) In Encouraging Regional Economic Growth - Nurdiana Kholida Oktaviana (Jurnal Ekonomi Kuantitatif Terapan, 2025)
This paper analyzes the impact of Tourism SEZs in encouraging regional economic growth asmeasured through GDP. Indonesia has advantages in terms of economy and geography, thisadvantage makes Indonesia have tourism potential in each region. However, there is a gap ininfrastructure and supporting facilities, so the Government of Indonesia through the RPJMNestablished a Tourism SEZ through collaboration with private companies to encourage economicgrowth in the area. In addition, this program is expected to measure the impact of Tourism SEZson regional economic growth and how the gap between regions is. This study uses the Differencein Difference method with Staggered Treatment Timing, with a time period of 2010-2022. Theresults of the estimate found that the Tourism SEZ did not have a positive and significantinfluence on regional economic growth. The impact on regional economic growth will only beseen in the long term. In addition, control variables such as population and regional expenditureshowed a positive influence, while population density variables had a negative influence onregional economic growth.